Integrative Activity of Mating Loci, Environmentally Responsive Genes, and Secondary Metabolism Pathways during Sexual Development of Chaetomium globosum - Zheng Wang (American Society for Microbiology, 2019)
ABSTRACT The origins and maintenance of the rich fungal diversity have been longstanding issues in evolutionary biology. To investigate how differences in expression regulation contribute to divergences in development and ecology among closely related species, transcriptomes were compared between Chaetomium globosum, a homothallic pathogenic fungus thriving in highly humid ecologies, and Neurospora crassa, a heterothallic postfire saprotroph. Gene expression was quantified in perithecia at nine distinct morphological stages during nearly synchronous sexual development. Unlike N. crassa, expression of all mating loci in C. globosum was highly correlated. Key regulators of the initiation of sexual development in response to light stimuli—including orthologs of N. crassa sub-1, sub-1-dependent gene NCU00309, and asl-1—showed regulatory dynamics matching between C. globosum and N. crassa. Among 24 secondary metabolism gene clusters in C. globosum, 11—including the cochliodones biosynthesis cluster—exhibited highly coordinated expression across perithecial development. C. globosum exhibited coordinately upregulated expression of histidine kinases in hyperosmotic response pathways—consistent with gene expression responses to high humidity we identified in fellow pathogen Fusarium graminearum. Bayesian networks indicated that gene interactions during sexual development have diverged in concert with the capacities both to reproduce asexually and to live a self-compatible versus self-incompatible life cycle, shifting the hierarchical roles of genes associated with conidiation and heterokaryon incompatibility in N. crassa and C. globosum. This divergence supports an evolutionary history of loss of conidiation due to unfavorable combinations of heterokaryon incompatibility in homothallic species. IMPORTANCE Fungal diversity has amazed evolutionary biologists for decades. One societally important aspect of this diversity manifests in traits that enable pathogenicity. The opportunistic pathogen Chaetomium globosum is well adapted to a high-humidity environment and produces numerous secondary metabolites that defend it from predation. Many of these chemicals can threaten human health. Understanding the phases of the C. globosum life cycle in which these products are made enables better control and even utilization of this fungus. Among its intriguing traits is that it both is self-fertile and lacks any means of propagule-based asexual reproduction. By profiling genome-wide gene expression across the process of sexual reproduction in C. globosum and comparing it to genome-wide gene expression in the model filamentous fungus N. crassa and other closely related fungi, we revealed associations among mating-type genes, sexual developmental genes, sexual incompatibility regulators, environmentally responsive genes, and secondary metabolic pathways.